Macropsychology: A Systematic Scoping Review of the Psychology Literature on Public Policy and Law - Moonika Moonveld; Joanne McVeigh (Behavioral Sciences)
Macropsychology examines the influence of macro-level factors such as policies and laws on our psychological well-being and how the field of psychology can be more effectively leveraged to influence them. While psychology has traditionally been focused at the individual level, a greater focus is needed on policies and laws at the macro level, including areas that are underpinned by psychological concerns such as human rights and social justice. Systematic scoping review methods based on the PRISMA guidelines were used to examine the following research question: To what extent is psychology, through macropsychology, engaging with public policy and law, particularly in relation to social justice? In total, 118 articles were identified as meeting the inclusion criteria, including 46 empirical articles and 72 conceptual articles. Although the authors of such articles are clearly operating at the macro level, it is not evident that they conceptualise such work as macropsychology. This scoping review is the first to systematically synthesise psychological research at the macro level, adding value to the existing conceptualisation of macropsychology. This review calls attention to the work of psychologists engaging with public policy and law from a social justice perspective.